RANCANG BANGUN MEDIA DIMETA-AR PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Maharani, Aziza; Sofwan, Muhammad; Risdalina, Risdalina (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
This study is motivated by the need for IPAS (Science and Social Sciences) learning that provides concrete learning experiences, particularly for metamorphosis material, which is abstract and difficult for third-grade elementary students to visualize. Initial observations at SDN 111/1 Muara Bulian showed that teachers still rely on conventional media such as textbooks and static images, causing students to struggle in understanding the stages of metamorphosis in sequence. The purpose of this research is to develop an Augmented Reality–based Metamorphosis Diorama (DIMETA-AR) as an innovative learning solution capable of presenting interactive 3D objects that are more concrete, engaging, and aligned with the characteristics of Phase B learners. This research uses the Research and Development (R&D) method with the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The media was developed using Canva for the physical diorama design and Assemblr EDU for creating 3D AR-based objects. Product validity was assessed by material experts, media experts, and language experts, while practicality was evaluated by teachers and students through questionnaires. The results of the study show that DIMETA-AR obtained a very high level of validity, achieving 97.5% from the material expert and the category of “very valid” from both the media and language experts. Practicality tests also indicate that the media was rated as “very practical” by teachers and students, with responses demonstrating that AR helped them understand metamorphosis more clearly and attractively. DIMETA-AR has been proven to enhance student engagement, encourage exploratory activities, and facilitate interactive, student-centered IPAS learning in accordance with the principles of the Merdeka Curriculum. Therefore, this media is appropriate for use in elementary science learning and has the potential to be further developed for other IPAS topics. ABSTRAK Penelitian ini dilatarbelakangi oleh kebutuhan pembelajaran IPAS yang menuntut pengalaman belajar konkret, terutama pada materi metamorfosis yang bersifat abstrak dan sulit divisualisasikan oleh peserta didik kelas III Sekolah Dasar. Observasi awal di SDN 111/1 Muara Bulian menunjukkan bahwa guru masih mengandalkan media konvensional berupa buku teks dan gambar statis sehingga siswa kesulitan memahami tahapan metamorfosis secara runtut. Tujuan penelitian ini adalah mengembangkan media Diorama Metamorfosis berbasis Augmented Reality (DIMETA-AR) sebagai solusi pembelajaran inovatif yang mampu menghadirkan objek 3D interaktif sehingga lebih konkret, menarik, dan sesuai dengan karakteristik peserta didik fase B. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang terdiri atas tahap Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Media dikembangkan menggunakan Canva untuk desain diorama fisik dan Assembler EDU untuk pembuatan objek 3D berbasis AR. Validitas produk dinilai oleh ahli materi, ahli media, dan ahli bahasa, sementara kepraktisan dinilai oleh guru dan siswa melalui angket. Hasil uji kepraktisan juga menunjukkan bahwa media dinilai “sangat praktis” oleh guru dan peserta didik, dengan respon yang menunjukkan bahwa AR membantu mereka memahami metamorfosis secara lebih jelas dan menarik. Media DIMETA-AR terbukti dapat meningkatkan keterlibatan siswa, mendorong aktivitas eksploratif, serta menghadirkan pembelajaran IPAS yang interaktif dan berpusat pada siswa sesuai prinsip Kurikulum Merdeka. Dengan demikian, media ini layak digunakan dalam pembelajaran sains di sekolah dasar dan berpotensi dikembangkan untuk materi IPAS lainnya